(untitled) (Journal of Information Technology and Digital World, 2023)
With a population of more than one billion, India is the largest democracy in the world. Its electorate is more than 668 million people and includes 543 congressional districts. Each Indian citizen above 18 years of age is entitled to vote in elections to choose their leaders. The traditional method of voting involved paper ballot voting and at present Electronic Voting Machines (EVM) are employed. The goal of the mobile voting system research is to create a software that makes voting simple in all elections. This system aims to increase election security by using a fingerprint recognition algorithm for voter identity authentication. This allows all eligible voters to participate in the election from any place. There are some circumstances like COVID epidemic where a physical election is not feasible, and this model overcomes it. It helps to provide reliable, timely, and accurate election results. Voter ID, Aadhar ID and biometric system (fingerprint) are used by the website for user login.